2016
DOI: 10.1007/s00101-016-0171-6
|View full text |Cite
|
Sign up to set email alerts
|

Brauner Urin

Abstract: Rhabdomyolysis is a rare but well-known complication of statin therapy. The risk is considerably increased when concomitant drugs are administered that inhibit metabolism and breakdown via the cytochrome CYP3A4. We report a case of myoglobin-induced acute renal failure secondary to the concomitant use of simvastatin and amiodarone. The risk of rhabdomyolysis is mainly determined by the statin dose; in the case of the concomitant use of CYP3A4 inhibitors, a maximal daily dose of 20 mg is recommended to avoid ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Nevertheless, patients with cardiovascular diseases would take several medicines which can result in combined adverse drug reaction. There were several studies reported about drug combination reaction caused rhabdomyolysis between simvastatin and amiodarone, which simvastatin is metabolized by CYP3A4 and amiodarone is a CYP3A4 inhibitor (Roten et al, 2004;Schmidt et al, 2007;Pietsch et al, 2016). The reaction could lead to secondary acute renal failure.…”
Section: Blood Chemistry Monitoringmentioning
confidence: 99%
“…Nevertheless, patients with cardiovascular diseases would take several medicines which can result in combined adverse drug reaction. There were several studies reported about drug combination reaction caused rhabdomyolysis between simvastatin and amiodarone, which simvastatin is metabolized by CYP3A4 and amiodarone is a CYP3A4 inhibitor (Roten et al, 2004;Schmidt et al, 2007;Pietsch et al, 2016). The reaction could lead to secondary acute renal failure.…”
Section: Blood Chemistry Monitoringmentioning
confidence: 99%